2017
DOI: 10.1037/bar0000039
|View full text |Cite
|
Sign up to set email alerts
|

A review of resurgence literature with human participants.

Abstract: Resurgence is the reemergence of a previously reinforced behavior when an alternative source of reinforcement is discontinued or decreased (Lattal & St. Peter Pipkin, 2009). Lattal and St. Peter Pipkin (2009) published a review in which they discussed the applied relevance of the resurgence literature, which was largely composed of investigations studying nonhuman subjects at the time. There has since been an increase in resurgence research with human participants. The purpose of the current paper is to review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Resurgence is defined as the reemergence of a previously extinguished response (e.g., destructive behavior) when the alternative response is exposed to extinction or large decreases in the rate of reinforcement (Doughty & Oken, ; Epstein, , ; Lattal et al, ; Lattal & St. Peter Pipkin, ; Leitenberg, Rawson, & Bath, ; Lieving, Hagopian, Long, & O'Connor, ; Lieving & Lattal, ; Podlesnik & DeLeon, ; Pritchard, Hoerger, & Mace, ; Winterbauer & Bouton, ). The study of resurgence represents an important area of investigation in both applied and translational research because it may form the basis of many or most occurrences of treatment relapse in typical environments (Kestner & Peterson, ; Lattal & St. Peter Pipkin, ; St. Peter, 2015). For example, individuals often emit the FCR at high rates or at inopportune times, when it is difficult for caregivers to deliver the requested reinforcer (Fisher et al, ; Hagopian et al, ; Tiger, Hanley, & Heal, ).…”
mentioning
confidence: 99%
“…Resurgence is defined as the reemergence of a previously extinguished response (e.g., destructive behavior) when the alternative response is exposed to extinction or large decreases in the rate of reinforcement (Doughty & Oken, ; Epstein, , ; Lattal et al, ; Lattal & St. Peter Pipkin, ; Leitenberg, Rawson, & Bath, ; Lieving, Hagopian, Long, & O'Connor, ; Lieving & Lattal, ; Podlesnik & DeLeon, ; Pritchard, Hoerger, & Mace, ; Winterbauer & Bouton, ). The study of resurgence represents an important area of investigation in both applied and translational research because it may form the basis of many or most occurrences of treatment relapse in typical environments (Kestner & Peterson, ; Lattal & St. Peter Pipkin, ; St. Peter, 2015). For example, individuals often emit the FCR at high rates or at inopportune times, when it is difficult for caregivers to deliver the requested reinforcer (Fisher et al, ; Hagopian et al, ; Tiger, Hanley, & Heal, ).…”
mentioning
confidence: 99%
“…Resurgence occurs with socially significant responses, including aggression (e.g., Pritchard, Hoerger, & Mace, 2014), disruptive behavior (e.g., Marsteller & St. Peter, 2014), self-injurious behavior (e.g., Wacker et al, 2011), property destruction (e.g., Mace et al, 2010;Wacker et al, 2013), and inappropriate vocal behavior (e.g., Marsteller & St. Peter, 2012). However, resurgence may be a desirable phenomenon when it is beneficial for responses to recur (Epstein, 1987;Kestner & Peterson, 2017;Shahan & Chase, 2002), such as appropriate requests (Hoffman & Falcomata, 2014), caregiving responses (Bruzek, Thompson, & Peters, 2009), play sequences (Reed & Clark, 2011), or phonetic responding (Garner, Neef, & Gardner, 2018). However, resurgence may be a desirable phenomenon when it is beneficial for responses to recur (Epstein, 1987;Kestner & Peterson, 2017;Shahan & Chase, 2002), such as appropriate requests (Hoffman & Falcomata, 2014), caregiving responses (Bruzek, Thompson, & Peters, 2009), play sequences (Reed & Clark, 2011), or phonetic responding (Garner, Neef, & Gardner, 2018).…”
mentioning
confidence: 99%
“…As this list suggests, applied evaluations of resurgence often assess the resurgence of undesirable, maladaptive behavior (e.g., Wacker et al, 2011). However, resurgence may be a desirable phenomenon when it is beneficial for responses to recur (Epstein, 1987;Kestner & Peterson, 2017;Shahan & Chase, 2002), such as appropriate requests (Hoffman & Falcomata, 2014), caregiving responses (Bruzek, Thompson, & Peters, 2009), play sequences (Reed & Clark, 2011), or phonetic responding (Garner, Neef, & Gardner, 2018).…”
mentioning
confidence: 99%
“…When the second play sequence was no longer reinforced, the children resumed the first play sequence. In the case of this study, resurgence did not delay an undesirable response; rather, resurgence demonstrated that a desirable response in an individual's repertoire persisted when periods of extinction occurred (Kestner & Peterson, 2017). Such longevity may be important for academic responses.…”
Section: Resurgence Of Academic Respondingmentioning
confidence: 57%
“…As this list suggests, resurgence of socially significant behavior is often studied in terms of the undesirable recurrence of maladaptive behavior (e.g., Wacker et al, 2011). However, resurgence may be a desirable phenomenon when it is beneficial for responses to recur (Epstein, 1987;Kestner & Peterson, 2017), such as appropriate requests (Hoffman & Falcomata, 2014), caregiving responses (Bruzek, Thompson, & Peters, 2009), and play sequences (Reed & Clark, 2011).…”
Section: Resurgence Of Academic Respondingmentioning
confidence: 99%